Microstructure, tensile properties and wear resistance correlations on directionally solidified Al-Sn-(Cu; Si) alloys - Bertelli, Felipe; Freitas, Emmanuelle S.; Cheung, Noé; Arenas, Maria A.; Conde, Ana; de Damborenea, Juan; Garcia, Amauri (Journal of alloys and compounds, 2017)
The development of alloys suitable for engine bearings demands not only reducing the amount of wear as well as increasing the load carrying capability due to both engines stop/start systems and sudden rise in load or velocity. Al-Sn based alloys are well-known for having excellent tribological and mechanical properties fulfilling these requirements: Sn is a self-lubricating component and addition of third elements should increase the strength of the Al-rich matrix. The current study focuses on interrelations of microstructure of directionally solidified Al-Sn(Cu; Si) alloys and mechanical/tribological properties. In order to analyze the influence of alloy Sn content on the tribological behavior of these ternary alloys, ball-on-disc wear tests were performed under dry sliding conditions. Correlations between tensile strength, elongation and wear volume and the primary dendritic arm spacing (λ1) have been determined. The worn samples were analyzed by scanning electron microscopy and energy dispersive spectroscopy (SEM-EDS) and the wear scar topographies by a confocal profilometer. The analysis of the worn surfaces revealed a change from abrasive to adhesive wear mechanism for Al-Sn-Cu alloys and only adhesive one for Al-Sn-Si alloys. For Al-Sn-Cu alloys, the best wear resistance was observed to be related to coarser microstructures whereas refined microstructures improved the tensile properties, indicating an inverse trend between tensile and tribological properties. The wear resistance of the Al-Sn-Si alloys were shown not to be affected by the size of λ1, however the tensile strength is shown to increase significantly with the decrease in λ1. [Display omitted] •Al-Sn-Si; Cu alloys microstructure: dendritic Al-matrix, Sn pockets and Si; Al2Cu particles.•The lower the dendritic spacing, λ1, > the tensile strength of Al-Sn-(Cu; Si) alloys.•The higher λ1, the higher the wear resistance for Al-Sn-Cu alloys.•Experimental equations relating wear volume/tensile properties vs. λ1 are proposed.